Correlation between Axial Length with Central Corneal Thickness and Degree of Myopia - Riska Andriani; Eddyanto Eddyanto (Majalah Oftalmologi Indonesia, 2016)
Background: The axial length (AL) elongation of the eyeball is the characteristc of myopia. If this is the result of general growth, one might expect the cornea to have grown to be thicker than normal. If instead the myopic eye is larger due to a mechanism of stretching, one would expect the cornea to be thinner than normal. Several studies to determine the relationship of central corneal thickness (CCT) and the AL have reported different results. This study aims to investigate the association between AL with CCT and degree of myopia. Methods: It was a cross sectional study, involved 60 eyes of 32 myopic subjects. Axial length was measured using an A-scan ultrasound, CCT was measured with an ultrasonic pachymeter, and refractive errors was measured with trial and error method.Results: Thirty-two patients (60 eyes) were recruited for the study. The age of patients ranged from 21 to 47 years old, with a mean of 27.6±7.58 years. The mean axial length was 23.98±0.81 mm and the mean CCT was 535.98±26.95 μm. There were 44 eyes with low myopia, 13 eyes with moderate myopia, and 3 eyes with high myopia. The analysis of covariance (Ancova) was used to verified correlation between AL and CCT (p=0.704). The Spearman’s correlation analysis was used to verified correlation between AL and degree of myopia (p=0.001). Conclusion: There was no correlation between AL and CCT. There was a significant positive correlation between AL and degree of myopia.  Keywords: AL, CCT, degree of myopia